(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper examines possible application of certain disperse materials based on iron powders as ferromagnetic sorbents for collecting the oil products spilled on the water surface. Sorption ability is defined for the investigated ferromagnetic sorbents.